Industrially produced trans fatty acids: major potential sources in Malaysian diet - A., Azimah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study was conducted to determine the major potential sources of industrially produced trans fatty acids (IP-TFAs) in Malaysian diet. Levels of IP-TFAs were initially determined in samples (n = 136) collected from 8 food groups (baked products, snacks, dairy products, breakfast cereals, fast foods, semisolid fats and cooking oils, and fried foods). A survey was carried out to 105 subjects aged 19-59 years old to determine the intake of IP-TFAs using Food Frequency Questionnaire (FFQ). The IP-TFAs range from 0-5.79% of food, with the highest found in semisolid fats and cooking oils (0.1-5.79%), followed by fast foods (0.04-0.86%), baked products (0.01-0.29%), breakfast cereals (0.06-0.45%), snacks (0.03-0.26%), dairy products (0-0.26%), and fried foods (0.002-0.06%). A Spearman’s Rho rank test showed that there were significant correlations (p < 0.05) between 4 of the food groups (semisolid fats and cooking oils, fast foods, fried foods, and baked products), with the total IP-TFA intakes of subjects. In general, total IP-TFAs intakes of subjects were < 1% of subjects’ diet (0.067%-0.91% of subjects’ total calorie intakes). This indicate that high fat foods (semisolid fats and cooking oils, fast foods, fried foods, and baked products) were the main contributor of IP-TFAs in Malaysian diet, despite the low proportion oftransfatty acids, following their high frequency of daily intake.